1993
DOI: 10.1007/bf02257402
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex differences of dehydroepiandrosterone sulfate (DHEAS) and cortisol (CRT) plasma levels in normal controls and Alzheimer's disease (AD)

Abstract: In 50 healthy subjects (23 female, 27 male, aged 18-81) and 24 patients with Alzheimer's disease (AD) (11 female, 13 male, aged 58-88) DHEAS and CRT plasma levels were studied. In normal subjects there was a clear negative correlation of DHEAS to age, while no significant age correlated decrease of CRT plasma levels was found. There was a significant decrease in the DHEAS/CRT ratio in elderly controls (aged > 60) as compared to young individuals (aged < 45). Overall there was a trend to lower DHEAS/CRT ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Recent studies suggested that DHEA-S may increase some cerebral acetylcholinergic-dependent functions and that its decline may be associated with a greater susceptibility to the damage from neuroexcitatory aminoacids (Rhodes et al, 1997;Kimonides et al, 1998). The evidence of an association between DHEA-S levels and dementia is much less definite in humans, and most studies on small series of patients including different subtypes of dementia reported conflicting results (Cuckle et al, 1990;Spath-Schwalbe et al, 1990;Schneider et al, 1992;Leblhuber et al, 1993;Barret-Connor and Edelstein, 1994;Legrain et al, 1995;Berr et al, 1996;Yaffe et al, 1998;Wolf et al, 1999;Hillen et al, 2000). Findings of the present study do not show a significant association between DHEA-S levels and DAT.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent studies suggested that DHEA-S may increase some cerebral acetylcholinergic-dependent functions and that its decline may be associated with a greater susceptibility to the damage from neuroexcitatory aminoacids (Rhodes et al, 1997;Kimonides et al, 1998). The evidence of an association between DHEA-S levels and dementia is much less definite in humans, and most studies on small series of patients including different subtypes of dementia reported conflicting results (Cuckle et al, 1990;Spath-Schwalbe et al, 1990;Schneider et al, 1992;Leblhuber et al, 1993;Barret-Connor and Edelstein, 1994;Legrain et al, 1995;Berr et al, 1996;Yaffe et al, 1998;Wolf et al, 1999;Hillen et al, 2000). Findings of the present study do not show a significant association between DHEA-S levels and DAT.…”
Section: Discussionmentioning
confidence: 93%
“…In a small case-control study, Sunderland et al (1989) observed lower DHEA levels in early Alzheimer's disease than in healthy subjects. Further studies, however, mostly with small series of patients, did not confirm these results (Cuckle et al, 1990;Spath-Schwalbe et al, 1990;Leblhuber et al, 1993). More recently, observational longitudinal studies failed to demonstrate a predictive role of DHEA levels with respect to development of cognitive decline (Barret-Connor and Edelstein, 1994;Berr et al, 1996;Yaffe et al, 1998), and a randomized trial did not show evidence of benefit from treatment with DHEA in patients with Alzheimer's disease (Wolkowitz et al, 2003).…”
Section: Introductionmentioning
confidence: 83%
“…Whether there is a link between reduced levels of DHEA or DHEAS and AD is still a controversial issue. Most studies have not found differences in DHEAS levels between AD patients and non-demented patients (Legrain et al, 1995;Yanase et al, 1996;Ferrario et al, 1999), whereas two studies have reported decreased levels of DHEAS in AD patients (Leblhuber et al, 1993;Murialdo et al, 2000). No apparent relationship between circulating levels of DHEAS and cognitive performance in the elderly has been found (Barrett-Connor and Edelstein, 1994;Kalmijn et al, 1998;Mazat et al, 2001;Yaffe et al, 1998a).…”
Section: Steroidal Aging In Humansmentioning
confidence: 99%
“…As described above, measures of blood levels of DHEA and DHEAS in AD patients have provided conflicting results (Leblhuber et al, 1993;Legrain et al, 1995;Yanase et al, 1996;Ferrario et al, 1999;Murialdo et al, 2000). A comparative analysis of the concentrations of several neurosteroids in various brain regions between aged AD patients and aged non-demented controls has been recently reported (Weill-Engerer et al, 2002).…”
Section: Analysis Of Neurosteroids In the Brains Of Aged Patients By mentioning
confidence: 99%
“…Declining DHEA and DHEA sulfate (DHEAS) levels during aging are associated with pathophysiological effects such as neuronal degeneration (Leblhuber et al, 1993). Recent studies show that DHEA protects rat chromaffin cells and PC12 rat pheochromocytoma cells against serum-deprivation induced apoptosis (Charalampopoulos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%